Remaking the Chinese City Modernity and National Identity, 1900-1950 - Buck, David; Esherick, Joseph 1942-; MacKinnon, Stephen; McIsaac, Lee; Musgrove, Charles; Rogaski, Ruth; Sheehan, Brett; Strand, David; Tsin, Michael; Wang, Liping; Wasserstrom, Jeffrey; Yue Dong, Madeleine (University of Hawaii Press, 2000)
In China today skyscrapers tower over ancient temples, freeways deliver lines of cars and tour buses to imperial palaces, cinema houses compete with old theaters featuring Peking Opera. The disparity evidenced in the contemporary Chinese cityscape can be traced to the early decades of the twentieth century, when government elites sought to transform cities into a new world that would be at once modern and distinctly Chinese. Remaking the Chinese City aims to capture the full diversity of recent Chinese urbanism by examining the modernist transformations of China's cities in the first half of the twentieth century.